Odpowiedzi

2010-02-12T17:56:22+01:00
4(-2r + s) - 10,5 r = -8r +4s - 10,5r = -18,5 r + 4s

-3(3x - 2y) + 2(x - 2y) = -9x + 6y + 2x - 4y = -7x + 2y

-5(2z - 3y) - 4(4z - 2y) = - 10z +15y -16z +8y = -26z + 23y

2(2p - 3q) - 4(4z - 2y) = 4p - 6q - 16z+ 8 y
2(3x - 2y + 5y) - 3(4y + 5y) + 2x - 3x = 6x - 4y +10y -12y -15y +2x = -21y + 8x
2 5 2
2010-02-12T17:58:03+01:00
4(-2r + s) - 10,5 r =-8r+4s-10,5r=-18,5r+4s

-3(3x - 2y) + 2(x - 2y) =-9x+6y+2x-4y=-7x+2y

-5(2z - 3y) - 4(4z - 2y) = -10z+15y-16z+8y=-26z+23y

2(2p - 3q) - 4(4z - 2y) =4p-6q-16z+8y

2(3x - 2y + 5y) - 3(4y + 5y) + 2x - 3x =
6x-4y+10y-12y-15y+2x-3x = 5x-23y
1 5 1
2010-02-12T22:53:04+01:00
4(-2r + s) - 10,5 r = -8r+4s-10,5r = -18,5r+4s
-3(3x - 2y) + 2(x - 2y) = -9x+6y+2x-4y = -7x+2y
-5(2z - 3y) - 4(4z - 2y) = -10z+15y-16z+8y = -26z+23y
2(2p - 3q) - 4(4z - 2y) = 4p-6q-16z+8y
2(3x - 2y + 5y) - 3(4y + 5y) + 2x - 3x = 6x-4y+10y-12y-15y+2x-3x = 5x-21y
1 4 1